Active labour market policy effects for women in Europe: A survey - Annette Bergemann; Gerard J. van den Berg (Institute for Fiscal Studies (IFS), 2006)
We survey the recent literature on the effects of active labor market policies on individual labor market outcomes like employment and income, for adult female individuals without work in European countries. We consider skilltraining programs, monitoring and sanctions, job search assistance, and employment subsidies. The results are remarkably uniform across studies. We relate the results to the relevant level of female labor force participation.
Keywords: 330; job search; female labor supply; wages; unemployment; schooling; training; monitoring; participation; Arbeitsmarktpolitik; Weibliche Arbeitskräfte; Arbeitslosigkeit; Einkommen; Europa